ISGF3, the transcriptional activator induced by interferon alpha, consists of multiple interacting polypeptide chains. - Fu, X Y (1990)
Interferon-stimulated gene factor 3 (ISGF3) is the ligand-dependent transcriptional activator that, in response to interferon treatment, is assembled in the cell cytoplasm, is translocated to the nucleus, and binds the consensus DNA site, the interferon-stimulated response element. We have purified ISGF3 and identified its constituent proteins: a DNA-binding protein of 48 kDa and three larger polypeptides (84, 91, and 113 kDa), which themselves do not have DNA-binding activity. The multisubunit structure of ISGF3 most likely reflects its participation in receiving a ligand-dependent signal, translocating to the nucleus, and binding to DNA to activate transcription.